Discrepancy between Norms and Reality: Structural Barriers to Employment Rights for Persons with Disabilities in Gorontalo City - Fayza Tazkia Suleman; Weny Almoravid Dungga; Abdul Hamid Tome (Fox Justi : Jurnal Ilmu Hukum, 2026)
This study analyzes the barriers to fulfilling the right to obtain employment for persons with disabilities in Gorontalo City, focusing on the discrepancy between legal norms and policy implementation as well as structural barriers in socio-cultural and accessibility aspects. Employing a juridical-empirical method with a socio-legal research approach, this study combines normative analysis of legislation with empirical studies through in-depth interviews and documentation studies. The research findings reveal two main problems. First, there is a sharp discrepancy between the mandate of Law Number 8 of 2016 and Gorontalo City Regional Regulation Number 3 of 2023, which mandate a 2% employment quota for persons with disabilities, and the reality that no persons with disabilities work within the Gorontalo City Government environment out of a total of 613 registered persons with disabilities. This implementation failure is caused by weak law enforcement, the non-integration of disability issues in regional planning and budgeting, and the absence of an integrated database. Second, structural barriers in the form of stigma and perspective discrimination, lack of understanding of reasonable accommodation, inaccessible infrastructure, and low levels of education and job training create a systematic vicious cycle of exclusion. This study recommends comprehensive policy interventions encompassing public perspective transformation, accessible infrastructure development, and sustainable capacity-building programs.